PEMAHAMAN MAHASISWA TERHADAP NORMA DAN ETIKA SERTA APLIKASINYA DALAM KEHIDUPAN - MUSLIM, MUSLIM (Pelita Bangsa Pelestari Pancasila, 2018)
Norms and ethics are formed because of the wide range of individual differences among students. As an individual creature, students have personality, interest, desire, life purpose which different from one another. In order, for all these differences do not lead to hostility, argument, disorder then be made to the rule or norm. The purpose of this research was to analyze the level of students comprehension of FKIP Bung Hatta University about the norms and ethics, describe about norms and ethics application of FKIP students in life, as well as to analyze the causes and consequences that arised when student of FKIP not comprehend about norms and ethics. This research is a descriptive exploratory research with a qualitative approach. Descriptive exploratory research served to see, know and reveal what their circumstances at the time of the research. This research was conducted of FKIP Bung Hatta University. The population of this research were all FKIP students majors are PING, PINDO, PPKn, PGSD, PTIK, P.Biologi, and PMAT where located on the second campus of the Bung Hatta University. This research concluded that students of FKIP Bung Hatta University in Padang generally has been comprehend about the norms and ethics at the college, which is 95.37% knew the rules, norms, ethics, morals are both in attitude and in the dress code. Students need to comprehend the rules of norms and ethics that apply on campus, because in that way become good campus atmosphere and quiet, could impact both on the study load of students are 86.11%, so, create a conducive atmosphere and was reached ideals them, can form a personality that is honest, polite, and noble that is 88.89%. Comprehension about the norms and ethics for student of FKIP need to know in depth and must be applied in life, due to the comprehension of the norms and ethics of the students will be better and will achieve his goal and his life will be a blessing and a devout and obedient to the existing rules and avoid wrong deed. In general, students have to apply the norms and ethics in their life that is 90.74% have to apply.